Novel design and analysis of a solar PVT system using LFR concentrator and nano-fluids optical filter. (October 2021) - Wang, Gang; Wang, Botong; Yuan, Xipeng; Lin, Jianqing; Chen, Zeshao
Abstract: The current study proposes a novel solar PV and thermal (PVT) system based on the combination of linear Fresnel reflector (LFR) concentrator and ITO-EG nano-fluids optical filter. Preparation and relevant measurements of the ITO nano-particles as well as the ITO-EG nano-fluids are conducted. The test results reveal that the optical filter has an average absorptivity of 30.9% in the spectrum range of 250.0–2500.0 nm. The solar concentration behaviour of the PVT system is revealed and the sensitivity analysis results of sun tracking error indicate that when the north-south tracking error is 0.2°, the overall optical efficiency is 90.12%, which means the PVT system has a relatively good adaptive faculty on sun tracking error. Theoretical thermodynamic calculation and CFD simulation methods are utilized to estimate the operation behaviour of the PVT system. The results demonstrate that the PVT system has a photoelectric conversion efficiency of 29.6% as well as a thermal efficiency of 18.52%. Parametric analysis results show that the thermal efficiency of the PVT system can be improved by increasing the inlet nano-fluids flow velocity as well as the ambient temperature, or by reducing the inlet nano-fluids temperature or convection heat transfer coefficient.